2014
DOI: 10.3998/jmmh.10381607.0008.203
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of Muslim young adults’ adaptation experiences in New Zealand

Abstract: Muslim youth living in Western countries are thought to face a variety of risks to their adjustment, although according to recent research they do not necessarily have negative outcomes in comparison to non-Muslims. In order to examine the complexities of development for Muslim youth in the West, it is necessary to have a comprehensive understanding of their lived experiences within their intercultural context. Therefore, this research study qualitatively investigated the indicators and determinants of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Half of the Participants mutually agreed that with bombing and attacks in the name of Islam and relative negative media broadcasting about Muslims, they felt discriminatory behaviors from host nationals and even faculty members. The findings were consistent with that of Stuart (2014) establishing that negative portrayal of media about Muslims provokes negative views about Muslims. Consequently, acculturation becomes challenging in an environment where religious orientation is a source of social tension (Stuart, 2014).…”
Section: Changes In Religious Practicesupporting
confidence: 89%
See 1 more Smart Citation
“…Half of the Participants mutually agreed that with bombing and attacks in the name of Islam and relative negative media broadcasting about Muslims, they felt discriminatory behaviors from host nationals and even faculty members. The findings were consistent with that of Stuart (2014) establishing that negative portrayal of media about Muslims provokes negative views about Muslims. Consequently, acculturation becomes challenging in an environment where religious orientation is a source of social tension (Stuart, 2014).…”
Section: Changes In Religious Practicesupporting
confidence: 89%
“…The findings were consistent with that of Stuart (2014) establishing that negative portrayal of media about Muslims provokes negative views about Muslims. Consequently, acculturation becomes challenging in an environment where religious orientation is a source of social tension (Stuart, 2014). Similar to the findings of another study conducted on Pakistani scholars, the participants of the current study were compelled to clear the misconceptions related to their nationality and ethnicity through their behavior and attitudes in the host culture (Haider, 2020).…”
Section: Changes In Religious Practicesupporting
confidence: 89%
“…In both countries, family obligations directly decreased behavioral problems as well as indirectly increasing positive adaptation (greater life satisfaction and fewer behavioral problems), but only in New Zealand were family obligations found to directly increase life satisfaction. Qualitative research with New Zealand Muslim young adults has found that obligations to the family encourage behavior that is in line with cultural and religious expectations, and that even though this can cause difficulties for young people, respon-sibilities to family (rather than to the self) tended to be a major driver of achievement (Stuart, 2014). However, in the same research, it was found that strong family obligations restrict autonomy, which is integral in achieving successful outcomes in a Western cultural environment, and therefore is related to increases of greater stress and conflict.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases challenges such as these present risks that induce acculturative stress (Berry, 2006a;Ward & Szabo, in press), which is associated with decrements in well-being and increased psychological symptoms, including depression, anxiety, and psycho-somatic problems (Berry, 2006a;Jibeen & Khalid, 2010;Miller, Kim, & Benet-Martínez, 2011;Romero & Roberts, 2003;Ward & Szabo, 2019). One of the most common risks that young Muslims face in New Zealand is discrimination (Stuart, 2014). This manifests itself in terms of everyday racism, negative stereotypes based on lack of knowledge about Islam, and unfavourable media portrayals of Muslims, as well as discrimination in educational and employment contexts (Ward, Lescelius, Naidu, Jack, & Weinberg, 2016).…”
Section: Risks Resources and Resiliencementioning
confidence: 99%